Modificação dos mesoporos da sílica MCM-41 com oxi-hidróxido de ferro e cálcio para aplicação em processos de adsorção - Adriana Barbosa Salviano (2017)
In this work, adsorbents based on MCM-41 treated at 550 900 ºC, impregnated with iron or calcium were treated at different temperatures and characterized by different techniques: powder XRD, superficial area BET, infrared, Raman, scanning and transmission electron microscopy, Mössbauer spectroscopy, programmed temperature reduction and zeta potential. The -lactam antibiotics adsorption results on MCM-41 impregnated with different iron proportions (5-50% wt) are presented. The obtained results suggest that both the Fe content and the treatment temperature of the materials strongly affect the antibiotics adsorption, and the best results were obtained for the 20Fe150 sample (20% Fe treatedat 150 ° C), ca. 12, 16 and 26 mg g-1, for cephalexin, ceftriaxone and amoxicillin (AMX), respectively. From the antibiotic adsorption studies and competitive adsorption experiments (AMX/phosphate and H2O2) it was possible to propose that the antibiotic molecules are probably adsorbed by complexation on Fe3+ surface species. These materials were also applied for the in adsorption of the model dye methylene blue (MB)and again the material that showed the best results was 20Fe150, ca. 104 mgMB g-1. From the MB adsorption assays, it was possible to conclude that the dye molecules are adsorbed by electrostatic and hydrogen interactions. Subsequently, the adsorbents produced from the treatment of MCM-41 at different temperatures were tested as phosphate (PHO) adsorption. The treatment temperature of MCM-41 significantly affects its pore arrangement and its adsorption capacity of PHO,with the best results obtained for the 550/MCM-41 sample (MCM-41 treated at 550 °C), ca. 61 mgPHO g-1. Finally, the materials obtained from the impregnation of calcium (5-50% wt) in the MCM-41 and the results of the oleic acid adsorption (OA) and biodiesel production tests are presented. Both the Ca content and the treatment temperature of the adsorbents affected OA removal, with the best results obtained for the 20Ca200 sample (20% Ca treated at 200 ° C), ca. 1.6 molOA molCa-1. From this results it was possible to suggest that the OA molecules complex with superficial Ca2+ species, giving rise to calciumoleate, which can be easily separated. Thus, these materials can be used as a "trap" for free fatty acids, allowing the synthesis of biodiesel from acid oils, using the basic homogeneous NaOH catalyst.